К вопросу об источниках Ибн Фадлана о народах Восточной Европы - Коновалова, И.Г. (Хазарский альманах, 2005)
Ибн Фадлан был первым - из известных нам - арабским путешественником, побывавшим в Восточной Европе. Это важное обстоятельство коренным образом повлияло из оценку достоверности приводимых им сведений о восточноевропейских народах. The article deals with the question of Ibn Fadlan's sources about states and people of Eastern Europe, in particular - with his personal means of gaining information during journey to the Volga-Bulgarians. The analysis is concentrated on such problems as Ibn Fadlan linguistic possibilities, the circle of his interlocutors on the different stages of the journey correlation between his written and oral sources. In conclusion it is stated the predominate of visual perception in the text of Ibn Fadlan's book, the absence of any author's reflections the mutual location of different states and settlements that he have seen and the lack attention on the part of Ibn Fadlan to the independent evaluation of the information called.